Museums and its endeavour to combat religious extremism-Iconoclasm: an analysis/ Rahimin Affandi Abdul Rahim, Muhd Imran Abd Razak and Mohd Anuar Ramli - Abdul Rahim, Rahimin Affandi; Abd Razak, Muhd Imran; Ramli, Mohd Anuar (Faculty of Information Management, 2021)
Religious extremism is an issue that threatens global peace especially the congruous image of Islam. This is further exacerbated by the philosophy of iconoclasm which is strongly held by the Wahhabis and Daesh have destroyed all the artifacts and historical monuments that exist in the Islamic world. Therefore, this study concentrates on museums and its endeavour to combat religious Extremism-Iconoclasm. Based on qualitative methods, the data is analyzed about the role of museums in addressing the philosophy of extreme iconoclasm involving Muslims. The findings found that the museum as an institution for the preservation and education of historical heritage is seen to be able to correct the negative image of Islam that has been tarnished by religious extremism. Therefore, this study has elaborated at length on how museums can be used to combat this iconoclasm philosophy. It considers what museums are working on in general in particular museums in Malaysia.